Automatic Stabilizers and Economic Crisis: US vs. Europe - Mathias Dolls; Clemens Fuest; Andreas Peichl (Verein für Socialpolitik, 2010)
This paper analyzes the effectiveness of the tax and transfer systems in the European Union and the US to act as an automatic stabilizer in the current economic crisis. We find that automatic stabilizers absorb 38 per cent of a proportional income shock in the EU, compared to 32 per cent in the US. In the case of an unemployment shock 48 per cent of the shock are absorbed in the EU, compared to 34 per cent in the US. This cushioning of disposable income leads to a demand stabilization of 17 to 33 per cent in the EU and 16 to 28 per cent in the US. There is large heterogeneity within the EU. Automatic stabilizers in Eastern and Southern Europe are much lower than in Central and Northern European countries. We also investigate whether countries with weak automatic stabilizers have enacted larger fiscal stimulus programs. We find no evidence supporting this view. However, we find that active fiscal policy is lower in more open economies.
Keywords: H20; H31; E63; 330; Automatic Stabilization; Crisis; Liquidity Constraints; Fiscal Stimulus